Findings of the Association for Computational Linguistics: EMNLP 2020 2020
DOI: 10.18653/v1/2020.findings-emnlp.407
|View full text |Cite
|
Sign up to set email alerts
|

Improving Aspect-based Sentiment Analysis with Gated Graph Convolutional Networks and Syntax-based Regulation

Abstract: Aspect-based Sentiment Analysis (ABSA) seeks to predict the sentiment polarity of a sentence toward a specific aspect. Recently, it has been shown that dependency trees can be integrated into deep learning models to produce the state-of-the-art performance for ABSA. However, these models tend to compute the hidden/representation vectors without considering the aspect terms and fail to benefit from the overall contextual importance scores of the words that can be obtained from the dependency tree for ABSA. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 22 publications
(16 reference statements)
0
13
0
Order By: Relevance
“…4) RGCN. Veyseh et al (2020) [54] regulate the GCN-based representation vectors based on the dependency trees in order to benefit from the overall contextual importance scores of the words.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…4) RGCN. Veyseh et al (2020) [54] regulate the GCN-based representation vectors based on the dependency trees in order to benefit from the overall contextual importance scores of the words.…”
Section: Methodsmentioning
confidence: 99%
“…[60] use a memory network to cache the sentential representations into external memory and then calculate the attention with the target aspect. Recently, Veyseh et al (2020) [54] regulate the GCN-based representation vectors based on the dependency trees in order to benefit from the overall contextual importance scores of the words.…”
Section: Sentiment Analysis and Opinion Miningmentioning
confidence: 99%
See 1 more Smart Citation
“…The key idea of the model is to use a gating mechanism to filter out irrelevant information, thereby uncovering crucial information related to aspect words. This method not only improves the accuracy of information extraction, but also helps the model gain a more comprehensive understanding of important information related to specific aspects in the text, thereby enhancing its performance in relevant tasks [ 25 ]. Zhao et al construct a graph taking aspects as nodes, and apply graph convolutional networks to extract inter-aspect sentiment dependencies for analyzing different aspects.…”
Section: Related Workmentioning
confidence: 99%
“…(1) These methods rely mainly on the semantic representation of sentences and ignore the syntactic information of the sentences. Recent studies 6,7 has shown that the introduction of syntactic analysis has improved the effectiveness of natural language processing.…”
Section: Introductionmentioning
confidence: 99%